The Coordination of Real Estate Economy and Market Economy Development - Han, Yanxiu (Journal of Theory and Practice of Management Science, 2023)
At present, the pillar industries of our economy have shifted from heavy industry to real estate enterprises. However, a failure to properly regulate and control the real estate industry and allow its development will certainly threaten the overall economic situation in our country. This paper briefly discusses the general situation of the development of real estate economy, and proposes some suggestions to strengthen the coordination of real estate economy and market economy, so as to strengthen the steady progress of our social economy.